El arco y el cetro: problemas de la palabra y el poder en los poemas homéricos - Zecchin de Fasano, Graciela Cristina (2005)
The present article analyses the semantic value contained in the epic formulae epea pteroenta and his variations as expression of the antagonisms proper of epic narrative. Its also analyses the way in which these antagonisms - among heroes, narrative modalities, modes of design of the plot and conceptions of power - are featured in two objects through repetitive use and symbolic value: the Bow and the Sceptre.
O presente artigo analisa o valor semântico contido na fórmula épica epea pteroenta e seus alomorfos como expressão dos antagonismos próprios do relato épico. Analisa, ainda, o modo pelo qual os ditos antagonismos - entre heróis, entre modalidades narrativas, entre diversos modos de desenho da trama e entre concepções de poder - se encontram cifrados em dois objetos de uso recorrente e de valor simbólico: o arco e o cetro.
Keywords: Homer; Iliad; Odyssey; Word; Power; Letras; Homero; Ilíada; Odisea; Palabra; Poder^lpt